Analysis of the influence of rosemary and grape seed extracts on oxidation the lipids of peking duck meat - Bozhko, Nataliia; Tischenko, Vasyl; Pasichnyi, Vasil; Marynin, Andriy; Polumbryk, Maksym (Eastern-European Journal of Enterprise Technologies, 2017)
The most common way of solving the problem of oxidative damage to meat products is the use of a variety of antioxidant food additives that allow the purposeful regulation of the processes of oxidation of the lipid fraction of meat systems. The study explores the effect of an antioxidant composition of rosemary and grape seed extracts on the course of oxidative processes in minced Peking duck meat. It has been determined that its introduction in an amount of 0.12–0.36 % helps slow down the hydrolytic oxidation of the minced meat lipids by 10.5–32.5 %. When the composition is introduced, the stabilization of peroxide oxidation of unsaturated fatty acids occurs. The biggest effect was obtained when adding 0.36 % of the additive, which reduced the PV by more than twice. The amount of secondary oxidation products was the smallest at the end of the storage period of minced meat in a sample with a composition concentration of 0.36 %, when the TBA value was 2.8±0.11 mg MA/kg, which is more than twice as low as the control. The obtained results prove the possibility of adding the composition of the plant extracts (up to 0.36 %) to improve the stability of meat products to the oxidation damage and to prevent the decline in the product quality.